(untitled) (Academicia Globe: Inderscience Research, 2024)
Currently, linguistic research is conducted in various areas. Of particular interest is the topic of cross-cultural communication, which arouses interest in its aspects and the relevance of its study. Cross-cultural communication is understood to be the process of interaction and exchange of information between people from different cultures. Understanding this process is important for effective communication and cooperation in the world. For our study, linguistic phenomena inherent in one of the aspects of communication studies are of interest.